Microscopically analyzed interface behavior characteristics of acid precipitation on asphalt surface - Tengjiang Yu (IWA Publishing, 2021)
It is generally believed that the interaction between acid precipitation and asphalt has an effect on the performance of drainage asphalt pavement, but studies on the interface behavior characteristics from microscopic analysis are rare. Therefore, molecular dynamics (MD) was used to simulate the interfacial transition zone of precipitation (neutral and acid) and asphalt in the study, and the interfacial behavior characteristics of precipitation on asphalt surface were microscopically analyzed. Additionally, the composition of acid precipitation was configured in the laboratory, and the contact angles of precipitation solutions (SO42− and NO3−) on asphalt surface also verified the interface behavior characteristics between acid precipitation and asphalt. The results showed that the interaction of acid precipitation and asphalt is stronger than that of neutral precipitation, which makes it more difficult to remove from the surface of drainage asphalt pavement. With the increase of service temperature for drainage asphalt pavement, the interaction energy increases. Under the coupling effect of acid precipitation and low service temperature, water damage to the drainage asphalt pavement is more easily induced. The results revealed the micro-effect of acid precipitation and service temperature on drainage efficiency of an asphalt surface, which has certain theoretical significance and practical value for the application and exploration of drainage asphalt pavement. HIGHLIGHTS Interaction energy between acid precipitation and asphalt is stronger.; As the service temperature rises, the interface behavior of precipitation on an asphalt surface becomes more visibly active.; The coupling of acid precipitation and low temperature will further increase the influence of drainage asphalt pavement.; Acid precipitation has a smaller contact angle, that is, better wettability.;